2021
DOI: 10.1002/ajhb.23575
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between rs9939609 FTO polymorphism with waist circumference and body fat is moderated by ponderal index at birth in youth

Abstract: Objective: The goal of this study was to analyze whether the relationship between the rs9939609 polymorphism of the fat mass and obesity-associated gene (FTO) with nutritional status is moderated by the ponderal index (PI) at birth in children and adolescents.Methods: A cross-sectional study evaluated 382 schoolchildren aged 6-17 years. Anthropometric variables such as waist circumference (WC), body mass index (BMI) and body fat percentage (BF%) were used to assess nutritional status. Weight and height at birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Dedoussis and teammates [ 81 ] examined the interaction effect of the rs9939609 polymorphism with breastfeeding on WC in two independent cohorts of European children, and obtained a consistent result that the A allele is correlated with a greater WC only in those with less than one month of breastfeeding ( p < 0.05). Quevedo Alves et al [ 82 ] investigated the interaction effect of the rs9939609 polymorphism with ponderal index at birth on WC in a group of Brazilian children and adolescents aged 6–17 years and found that the subjects with the AA genotype had a higher average WC than those with the AT or TT genotype in the lower tertile (β = 4.40, p = 0.048), but not in the middle or upper tertile, of the ponderal index.…”
Section: Some Genetic Polymorphisms Of Fto Increas...mentioning
confidence: 99%
“…Dedoussis and teammates [ 81 ] examined the interaction effect of the rs9939609 polymorphism with breastfeeding on WC in two independent cohorts of European children, and obtained a consistent result that the A allele is correlated with a greater WC only in those with less than one month of breastfeeding ( p < 0.05). Quevedo Alves et al [ 82 ] investigated the interaction effect of the rs9939609 polymorphism with ponderal index at birth on WC in a group of Brazilian children and adolescents aged 6–17 years and found that the subjects with the AA genotype had a higher average WC than those with the AT or TT genotype in the lower tertile (β = 4.40, p = 0.048), but not in the middle or upper tertile, of the ponderal index.…”
Section: Some Genetic Polymorphisms Of Fto Increas...mentioning
confidence: 99%